Artificial energy inputs into spruce lowland forests in suburban landscapes in Slovenia - Pirnat, Janez (Zbornik gozdarstva in lesarstva, 2009)
Slovene forestry is concerned with nature conservation, but in the past, the species variety of forests has often been changed and, similarly as elsewhere in Europe, the share of forest with artificial dominance of Norway spruce increased. Based on the spatial model of landscape structure, we estimated the arrangement in conservation of suburban forests in eight Slovene macro regions. In the area of town Kočevje, we assessed artificial energy inputs in the forests lying within one kilometre large area used by inhabitants for daily recreation. In this area, 65 % of forests were categorized as forests with artificial dominance of Norway spruce.
Keywords: gozdovi; krajina; Picea abies L.; Slovenia; Slovenija; smreka